Perencanaan Strategik Pendirian Ma’had Aly Pondok Quran Bandung - Seftiani, Rizka Dwi; Hafshoh, Siti Dieny; Irawan, Irawan (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2018)
This research focuses on the process of strategic planning completion of the Ma'had Aly Pondok Quran establishment in Bandung Regency. This research uses Kurt Lewin model of action research method which consists of planning, acting and fact finding on the result of the action. The results of this study indicate that there are several efforts to meet the conditions that have been determined by the Minister of Religious Regulation 71/2015 on the establishment of Ma'had Aly Pondok Quran. The contributing factors of the succesful strategic planning are the results of the present and expected future conditions analysis, the results of Ma'had Aly SWOT analysis, the Master Plan Development Document (RIP)of Ma'had Aly Pondok Quran, Strategic Plan Cycles and Strategic Plan Matrix of the Ma'had Aly performance. These constitute as the guidelines for the realization of the ideal establishment of Ma'had Aly which is in accordance with the Guide of Establishment of Ma'had Aly as stated on the operational guidelines of the Ministry of Religious Affairs.